Global, regional, and national age-sex-specific burden of diarrhoeal diseases, their risk factors, and aetiologies, 1990–2021, for 204 countries and territories: a systematic analysis for the Global Burden of Disease Study 2021 - Hmwe Hmwe, Kyu (2024)
BackgroundDiarrhoeal diseases claim more than 1 million lives annually and are a leading cause of death in children younger than 5 years. Comprehensive global estimates of the diarrhoeal disease burden for specific age groups of children younger than 5 years are scarce, and the burden in children older than 5 years and in adults is also understudied. We used results from the Global Burden of Diseases, Injuries, and Risk Factors Study 2021 to assess the burden of, and trends in, diarrhoeal diseases overall and attributable to 13 pathogens, as well as the contributions of associated risk factors, in children and adults in 204 countries and territories from 1990 to 2021. MethodsWe used the Cause of Death Ensemble modelling strategy to analyse vital registration data, verbal autopsy data, mortality surveillance data, and minimally invasive tissue sampling data. We used DisMod-MR (version 2.1), a Bayesian meta-regression tool, to analyse incidence and prevalence data identified via systematic reviews, population-based surveys, and claims and inpatient data. We calculated diarrhoeal disability-adjusted life-years (DALYs) as the sum of years of life lost (YLLs) and years lived with disability (YLDs) for each location, year, and age–sex group. For aetiology estimation, we used a counterfactual approach to quantify population-attributable fractions (PAFs). Additionally, we estimated the diarrhoeal disease burden attributable to the independent effects of risk factors using the comparative risk assessment framework. FindingsIn 2021, diarrhoeal diseases caused an estimated 1·17 million (95% uncertainty interval 0·793–1·62) deaths globally, representing a 60·3% (50·6–69·0) decrease since 1990 (2·93 million [2·31–3·73] deaths). The most pronounced decline was in children younger than 5 years, with a 79·2% (72·4–84·6) decrease in diarrhoeal deaths. Global YLLs also decreased substantially, from 186 million (147–221) in 1990 to 51·4 million (39·9–65·9) in 2021. In 2021, an estimated 59·0 million (47·2–73·2) DALYs were attributable to diarrhoeal diseases globally, with 30·9 million (23·1–42·0) of these affecting children younger than 5 years. Leading risk factors for diarrhoeal DALYs included low birthweight and short gestation in the neonatal age groups, child growth failure in children aged between 1–5 months and 2–4 years, and unsafe water and poor sanitation in older children and adults. We estimated that the removal of all evaluated diarrhoeal risk factors would reduce global DALYs from 59·0 million (47·2–73·2) to 4·99 million (1·99–10·0) among all ages combined. Globally in 2021, rotavirus was the predominant cause of diarrhoeal deaths across all ages, with a PAF of 15·2% (11·4–20·1), followed by norovirus at 10·6% (2·3–17·0) and Cryptosporidium spp at 10·2% (7·03–14·3). In children younger than 5 years, the fatal PAF of rotavirus was 35·2% (28·7–43·0), followed by Shigella spp at 24·0% (15·2–37·9) and adenovirus at 23·8% (14·8–36·3). Other pathogens with a fatal PAF greater than 10% in children younger than 5 years included Cryptosporidium spp, typical enteropathogenicEscherichia coli, and enterotoxigenic E coli producing heat-stable toxin. InterpretationThe substantial decline in the global burden of diarrhoeal diseases since 1990, particularly in children younger than 5 years, supports the effectiveness of health interventions such as oral rehydration therapy, enhanced water, sanitation, and hygiene (WASH) infrastructure, and the introduction and scale-up of rotavirus vaccination. Targeted interventions and preventive measures against key risk factors and pathogens could further reduce this burden. Continued investment in the development and distribution of vaccines for leading pathogens remains crucial. FundingBill & Melinda Gates Foundation.